2020
DOI: 10.1016/j.neuron.2020.07.013
|View full text |Cite
|
Sign up to set email alerts
|

Selective Mesoaccumbal Pathway Inactivation Affects Motivation but Not Reinforcement-Based Learning in Macaques

Abstract: Highlights d Reversible inactivation of the VTA-to-NAc pathway was achieved in monkeys d Mesoaccumbal circuit inactivation reduced high-effort motivational behavior d Unexpectedly, this perturbation did not affect reinforcementbased learning d The inactivation increased functional connectivity mainly in fronto-temporal circuits

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
3
2

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 69 publications
3
23
0
Order By: Relevance
“…After the injection sites relative to the grid were decided, the monkey was anesthetized again and the AAV vectors were injected into the intended location: the VTA. The injection needles were prepared as previously described ( Vancraeyenest et al. 2020 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…After the injection sites relative to the grid were decided, the monkey was anesthetized again and the AAV vectors were injected into the intended location: the VTA. The injection needles were prepared as previously described ( Vancraeyenest et al. 2020 ).…”
Section: Methodsmentioning
confidence: 99%
“…2006 ), motor behavior ( Kunori et al. 2014 ), attention ( Noudoost and Moore 2011 ) and motivation and effort ( Walton and Bouret 2019 ; Vancraeyenest et al. 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Recent advances in specific neuronal manipulation tools have drastically enhanced our understandings of the functional roles of individual neural pathways in small animals such as rodents (24,53). Nonetheless, the application of pathway-selective manipulations to non-human primates is still largely limited by using either optogenetic terminal activation (19)(20)(21) or double-vector methods (15)(16)(17)(18), neither of which is capable of testing dissociable function of multiple neural pathways in individual subjects. Using a chemogenetic approach, the current study succeeded in the double-dissociation of the roles of two distinct pathways in individual monkeys.…”
Section: R a F Tmentioning
confidence: 99%
“…Several studies have so far shown behavioral modification with reversible pathway-selective dissection in monkeys, where a double-viral vector infection method was used to manipulate the activity of a single neuronal pathway (15)(16)(17)(18). This approach, however, is not suitable for investigating multiple neural pathways independently within a single animal.…”
Section: Introductionmentioning
confidence: 99%
“…In another recent study, the technique was used in combination with functional imaging in monkeys performing cognitive tasks (Vancraeyenest et al, 2020). Specifically, the authors reversibly inactivated the connections originating in the ventral tegmental area (VTA) and projecting to the nucleus accumbens (NAc) in monkeys.…”
Section: Directional and Pathway-selective Approachesmentioning
confidence: 99%